1987
DOI: 10.1002/micr.1920080205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lidocaine concentration on distal capillary blood flow in a rabbit ear model

Abstract: The laser pulse doppler provides a noninvasive, reproducible method to measure the flux in distal capillary blood flow in a rabbit ear model. The distal capillary blood flow responds proportionally to changes in periarterial lidocaine concentration. The response is biphasic. Flow initially decreased from the baseline in all lidocaine concentrations between 0.5% and 10.0%. Proportional increases in distal blood flow above baseline are noted as the buffered lidocaine concentrations increase from 1.0% to 10.0%. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…We found that the iontophoresis of lidocaine HCl 4% did not increase perfusion of port‐wine stains above baseline. Periarterial infiltration of lidocaine 4% in the rabbit ear model showed a biphasic response of distal skin perfusion: intitial reduction in flux was replaced after 6 minutes with hyperperfusion 17 . Iontophoresis of lidocaine is capable of increasing skin perfusion in normal skin 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the iontophoresis of lidocaine HCl 4% did not increase perfusion of port‐wine stains above baseline. Periarterial infiltration of lidocaine 4% in the rabbit ear model showed a biphasic response of distal skin perfusion: intitial reduction in flux was replaced after 6 minutes with hyperperfusion 17 . Iontophoresis of lidocaine is capable of increasing skin perfusion in normal skin 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous solutions of lidocaine have been widely used topically to treat vasospasm in microvascular surgery (5). Higher concentrations of lidocaine have been recommended for faster resolution of vasospasm (3,6,7).…”
mentioning
confidence: 99%
“…Although numerous agents have been studied, we decided to compare papaverine and 1% lidocaine because these are two of the more commonly used agents clinically. Lidocaine has been used for many years in microvascular surgery, 1,2 and papverine is the agent of choice for microvascular procedures at our institution.…”
Section: Discussionmentioning
confidence: 99%